Occurrence of Pinus merkusii and Vegetational Analysis of its Forest from Arunachal Pradesh, India - Naithani, H. B. (Indian Forester, 2016)
Pinus merkusii is the only pine that occur naturally in south of the equator, distributed in Myanmar, Lao, Cambodia, Vietnam, South China. It has been reported from Anjow district, Arunachal Pradesh, India. Its detail description, distribution, uses, photographs and vegetative analysis for its associated, density, frequency and abundance has been mentioned.